Navigating the Turbulent Development of KF-21 Project between South Korea and Indonesia - Abel Manullang (Jurnal Alternatif - Jurnal Ilmu Hubungan Internasional, 2023)
South Korea and Indonesia are no strangers in defense cooperation. The two states have been working together on a project to develop a military jet called the KFX-IFX project. However, the project's ups and downs spark questions of what lies ahead for both the project and the two states. Through the use of the qualitative research method, the article makes use of numerous secondary data to answer its research questions. To enhance the analysis, relevant concepts, like defense diplomacy and rational choice theory, are also utilized. Starting off, the article begins with explanations over the KF-IFX jet project development. The project has witnessed some negative developments that have arisen from Indonesia's tardiness in paying its share. Following that, a discussion over the driving force behind South Korea and Indonesia's defense diplomacy is provided. On this matter, the factors can be understood in terms of the benefit given to the international reputation, confidence building as well as towards capacity building of both states. After that, the article touches upon the rationality behind Indonesia's move to maintain its commitment in the project. For this, the article finds that Indonesia has a lot at stake hence abandoning the project would not be beneficial.